Comparison of the ant assemblages in three phytophysionomies: Rocky field, secondary forest, and riparian forest - A case study in the state park of Ibitipoca, Brazil - Lopes, Juliane Floriano Santos; Hallack, Noelle Martins Dos Reis; Sales, Tatiane Archanjo De; Brugger, Mariana Silva [UNESP]; Ribeiro, Laila Fieto; Hastenreiter, Isabel Neto; Camargo, Roberto Da Silva (Hindawi, 2012)
Ant assemblages are almost all related with the vegetation composition and so can provide us important information for conservation strategies, which are especially relevant to an environmentally protected area. We sampled the ant fauna in three different phytophysionomies in order to verify if the composition of ant species is different among the areas, especially because one of the areas is a Rocky Field and there is little information about the ant fauna in this habitat. A total of 8730 individuals were registered and an NMDS analysis showed that the ant assemblies are different at the three phytophysionomies (Rocky Field, Riparian Forest, and Secondary Forest). This study shows that the species that compose the ant assemblies in different phytophysionomies are a reflex of the environment, supporting the hypothesis that the vegetational composition results in different compositions in the ant assembly. Vegetal composition is determinant in the formation of the litter and consequently in the occurrence of ant species that depend on this layer of organic matter for nesting and foraging. © 2012 Juliane Floriano Santos Lopes et al.